Age, height, BMI and FBG predict prostate volume in ageing benign prostatic hyperplasia: Evidence from 5285 patients. Issue 12 (25th October 2019) - Meng, Jialin; Liu, Yi; Guan, Shi-Yang; Ma, Huiya; Zhang, Xiaoyu; Fan, Song; Hu, Huaqing; Zhang, Meng; Liang, Chaozhao
Abstract: Aims: Several studies have reported a potential association between prostate volume (PV) and prostate disease. Here, we classified the risk factors for PV among benign prostatic hyperplasia (BPH) patients. Methods: In all, 4293 BPH patients with available clinical information were enrolled. Body mass index (BMI) was obtained as weight divided by height squared. PV was calculated as length × width × height (cm) × π/6. Mann‐Whitney U tests were used to determine the differences between PV subgroups. Univariate and multiple linear regression tests were performed to uncover the connection between clinical features and PV. The differences in the age, BMI, height and fasting blood glucose (FBG) of the subgroups were evaluated by Kruskal‐Wallis tests and adjusted with Bonferroni post hoc correction. A nomogram was created to directly illustrate the mutual interaction of amalgamator parameters. Results: PV did not influence the incidence of kidney stones ( P = .815), whereas prostate calculi were positively associated with an enlarged prostate (>30 mL) ( P < .001). Age (adjusted R = 0.363, P < .001), height (adjusted R = 0.088, P < .001), BMI (adjusted R = 0.039, P = .013) and FBG (adjusted R = −0.034, P = .027) were the independent risk/protective factors related to enlarged PV among BPH patients. The nomogram illustrated the predictive risk of an enlarged prostate (>30 mL) in men. The area under the ROC curve value was 0.659 in the training cohort and 0.677 in an internal validation cohort. Conclusions: Age, height and BMI were positive independent risk factors of enlarged PV in BPH patients, and FBG had a protective role.